GURITA KORUPSI PEMERINTAH DAERAH (THE ROOTS OF CORRUPTION OF THE LOCAL GOVERNMENTS) - Muhtar Haboddin; Fathur Rahman; Romi Yati (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Corruption is not something taboo in this country. The mass media, facts and data have revealed a variety of corruption cases in the central and regional governments, even there were cases involving a large number of people. Corruption involving a group of people is committed by both high and low ranking officials. This book reveals the facts on corruption at various levels the government. The lure of money that could not be resisted has become a personal benefit and very common. The crisis of shame has been epidemic until the level of local government. This book is rich in information revealing facts and data on corruption cases in a comprehensive way, and at the same time discussing them in a critical and systematic way.